Tin-Doped Indium Oxide-Titania Core-Shell Nanostructures for Dye-Sensitized Solar Cells - Luping Li; Cheng Xu; Yang Zhao; Kirk J. Ziegler (Advances in Condensed Matter Physics)
Dye-sensitized solar cells (DSSCs) hold great promise in the pursuit of reliable and cheap renewable energy. In this work, tin-doped indium oxide (ITO)-TiO2 core-shell nanostructures are used as the photoanode for DSSCs. High-density, vertically aligned ITO nanowires are grown via a thermal evaporation method and TiO2 is coated on nanowire surfaces via TiCl4 treatment. It is found that high TiO2 annealing temperatures increase the crystallinity of TiO2 shell and suppress electron recombination in the core-shell nanostructures. High annealing temperatures also decrease dye loading. The highest efficiency of 3.39% is achieved at a TiO2 annealing temperature of 500°C. When HfO2 blocking layers are inserted between the core and shell of the nanowire, device efficiency is further increased to 5.83%, which is attributed to further suppression of electron recombination from ITO to the electrolyte. Open-circuit voltage decay (OCVD) measurements show that the electron lifetime increases by more than an order of magnitude upon HfO2 insertion. ITO-TiO2 core-shell nanostructures with HfO2 blocking layers are promising photoanodes for DSSCs.